Seasonal Regional Differentiation of Human Thermal Comfort Conditions in Algeria - Salah Sahabi Abed; Andreas Matzarakis (Advances in Meteorology)
The thermal conditions of the bioclimate of Algeria are investigated applying especially the physiologically equivalent temperature (PET) seasonal variability of five main Algerian cities representing different climate and geographical conditions: coastal region, highland region, and Sahara zone. The physiologically equivalent temperature (PET) calculated for this study at 12.00 UTC (13.00 local time) is used to emphasize the impacts of climate on human heat stress in different seasonal and regional regimes. This study is important since it is performed for the first time in Algeria using a deterministic approach through the calculation of PET based on the body-atmosphere energy balance using the Munich Energy-Balance Model for Individuals (MEMI). Applying PET is a new feature in assessing the bioclimate of Algeria and serves the touristic and the health sector in particular. For touristic purposes, it is part of the new internationally introduced climate touristic/transfer information scheme (CTIS) enabling the Algerian results to be paled in comparison to other countries. Considering climate change, the study shows as a new feature a significant increase in the number of days with strong and extreme heat stress within the last three decades and discusses the risks and advantages for future tourism in Algeria.